2023
DOI: 10.1029/2022jb026045
|View full text |Cite
|
Sign up to set email alerts
|

Seismotectonics of the Blanco Transform Fault System, Northeast Pacific: Evidence for an Immature Plate Boundary

Abstract: At the Blanco transform fault system (BTFS) off Oregon, 138 local earthquakes and 84 double‐couple focal mechanisms from ocean‐bottom‐seismometer recordings jointly discussed with bathymetric features reveal a highly segmented transform system without any prominent fracture zone traces longer than 100 km. In the west, seismicity is focused at deep troughs (i.e., the West and East Blanco, and Surveyor Depressions). In the east, the BTFS lacks a characteristic transform valley and instead developed the Blanco Ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 73 publications
(246 reference statements)
0
4
0
Order By: Relevance
“…They found that the seismic slip is well constrained by the 600°C cutoff depth. However, microseismicity constrained by the local OBS array indicates that the brittle seismogenic zone of the Blanco OTF can penetrate to depths below the 600°C isotherm (Kuna et al., 2019; Ren et al., 2023). The microseismicities and petrological studies sampled from other OTFs have also reported semibrittle deformation at temperatures higher than 600°C (Kohli et al., 2021; Prigent et al., 2020; Yu et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…They found that the seismic slip is well constrained by the 600°C cutoff depth. However, microseismicity constrained by the local OBS array indicates that the brittle seismogenic zone of the Blanco OTF can penetrate to depths below the 600°C isotherm (Kuna et al., 2019; Ren et al., 2023). The microseismicities and petrological studies sampled from other OTFs have also reported semibrittle deformation at temperatures higher than 600°C (Kohli et al., 2021; Prigent et al., 2020; Yu et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the seismicity gap between 23 and 25 km corresponds to the deepest section of the western valley and the dense seismicity patch between 34 and 40 km is located beneath an along‐transform ridge (Figure 1 and Figure S6 in Supporting Information ). These valleys and ridges might have been formed as the local tectonic system evolves, affecting regional stress field and causing fault segmentation into distinct patches (Dewey et al., 1998; Gregg et al., 2006; Grevemeyer et al., 2021; Ren et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Microseismicity provides valuable insights into the fault structure, slip mode, and tectonic processes at OTFs (e.g., Gong & Fan, 2022; Gong et al., 2022; Kuna et al., 2019; McGuire et al., 2012; Ren et al., 2023; Wolfson‐Schwehr et al., 2014; Yu et al., 2021). We introduce a new workflow for detecting and locating microearthquakes using machine learning techniques.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation